# FIFO cogs

anyone explain the rationale behind this formula: FIFO COGS = LIFO COGS - (CHANGE IN LIFO RESERVE)

The LIFO reserve is a reconciling item, which reconciles COGS from LIFO to FIFO. In a rising price environment, COGS would be higher under LIFO (because it’s using the higher cost ‘last’ inventory, instead of the lower cost ‘first’ inventory to determine COGS), so you would subtract off a value to convert to FIFO. ETA: In a declining price environment, the number would be negative (so you would subtract a negative, or increase LIFO COGS) - in a declining price environment the opposite of what is down previously occurs.

Recall that " COGS = BEGINNING INVENTORY - ENDING INVENTORY + PURCHASES so: FIFO COGS = BEGINNING FIFO - ENDING FIFO + PURCHASE = BEGIN LIFO + BEGIN LIFO RESERVE - ENDING LIFO - ENDING LIFO RESERVE + PURCHASE do some rearranging you will have FIFO COGS = LIFO COGS - (BEGIN LIFO RESERVE - ENDING LIFO RESERVE).

The formula is in the FSA book as a footnote. I will try to remember it. First know that Life reserve=inventory(Lifo)-Inventory(Fifo) Also you know that Ending Inventory =Beginning inventory +purchases-COGS this is also true Ending Inventory(Lifo) =Beginning inventory(Lifo) +purchases-COGS(Lifo) Ending Inventory(Fifo) =Beginning inventory(Fifo) +purchases-COGS(Fifo) Notice that “purchases” is the same in both the above formulas do alittle algebra, that is get “purchases” by itself in both formulas and set them equal to eachother Ending Inventory(Lifo)- Beginning inventory(Lifo)+ COGS(Lifo)= Ending Inventory(Fifo)- Beginning inventory(Fifo)+ COGS(Fifo) Solve for COGS(Fifo) [Ending Inventory(Lifo)- Ending Inventory(Fifo)]-[Beginning inventory(Lifo)- Beginning inventory(Fifo)]+ COGS(Lifo)= COGS(Fifo) I hope I got this right.

Ako Wrote: ------------------------------------------------------- > The formula is in the FSA book as a footnote. I > will try to remember it. > > First know that > Life reserve=inventory(Fifo)-Inventory(Lifo) > > Also you know that > Ending Inventory =Beginning inventory > +purchases-COGS > > this is also true > Ending Inventory(Lifo) =Beginning inventory(Lifo) > +purchases-COGS(Lifo) > Ending Inventory(Fifo) =Beginning inventory(Fifo) > +purchases-COGS(Fifo) > > Notice that “purchases” is the same in both the > above formulas > do alittle algebra, that is get “purchases” by > itself in both formulas and set them equal to > eachother > > Ending Inventory(Lifo)- Beginning inventory(Lifo)+ > COGS(Lifo)= Ending Inventory(Fifo)- Beginning > inventory(Fifo)+ COGS(Fifo) > > Solve for COGS(Fifo) > -[Beginning inventory(Lifo)- Beginning > inventory(Fifo)]+ COGS(Lifo)= COGS(Fifo) > > I hope I got this right. Please ignore my above post use this Under either LIFO or FIFO the following equality always holds: EI = BI + Purchases - COGS Set up this equation for both LIFO and FIFO. FIFO: EIF = BIF + Purchase - COGSF LIFO: EIL = BIL + Purchase - COGSL Subtract the second equation from the first: (EIF - EIL) = (BIF + Purchases– COGSF )- (BIL+ Purchases- COGSL) = BIF + Purchases– COGSF - BIL- Purchases + COGSL = BIF – COGSF - BIL + COGSL = (BIF - BIL) – COGSF + COGSL = (BIF - BIL) + COGSL - COGSF (EIF - EIL) - (BIF - BIL) = (COGSL- COGSF)

“anyone explain the rationale behind this formula: FIFO COGS = LIFO COGS - (CHANGE IN LIFO RESERVE)” I think of it this way. The change in the LIFO reserve captures how many more dollars were expensed in LIFO COGS as compared to FIFO COGS since the firm has been using LIFO. Rearranging: Change in LIFO Reserve = LIFO COGS - FIFO COGS A company, according to GAAP, must set up a LIFO reserve contra account if using LIFO.